The Association between Hospital-Physician Vertical Integration and Outpatient Physician Prices Paid by Commercial Insurers: New Evidence - James Godwin BA; Daniel R. Arnold PhD; Brent D. Fulton PhD, MBA; Richard M. Scheffler PhD (SAGE Publishing, 2021)
This study assessed the relationship between hospital ownership of physician organizations (known as hospital-physician vertical integration) and facility fees billed to commercial insurers and physician service prices. Healthcare claims came from the IBM® MarketScan® Commercial Database (2012-2016, N = 30,716,800 office visit claims [CPT codes 99211-99215]), and hospital-physician vertical integration measures were from SK&A Office Based Physicians Database provided by IQVIA. Multi-variate, fixed-effect models were used to regress prices on market-level hospital-physician vertical integration; models included geographic market and year fixed effects, claim-level variables, and time-varying market-level variables. Analyses did not find that market-level hospital-physician vertical integration was associated with the billing of facility fees for office visits. However, vertical integration was associated with office visit physician prices for some specialties. A 10-percentage-point increase in vertical integration was associated with a 1.0% price increase for primary care, a 0.6% increase for orthopedics, and a 0.5% increase for cardiology; no such association was found for obstetrics/gynecology or oncology. When comparing metropolitan statistical areas (MSAs) in the bottom quartile of changes in vertical integration from 2012 to 2016 to MSAs in the top quartile, we found the following relative price increases based on predicted values for claims in the top quartile: $1.64 (1.9% of mean 2012 predicted price) for primary care to $2.30 (3.1%) for orthopedics to $3.13 (3.4%) for cardiology. Differences in predicted price accounted for an estimated $45.8 million in additional expenditure on primary care office visits in the top quartile of MSAs in 2016. In summary, market-level hospital-physician vertical integration was positively associated with physician prices for select specialties, but was not associated with changes in the use of facility-fee billing. More evidence on the quality effects of hospital-physician vertical integration is needed, as price increases that are not accompanied by measurable quality improvements should be part of any regulatory review.